POTENSI PENGEMBANGAN USAHA PETERNAKAN AYAM BURAS PADA UNIT PELAKSANAAN TEKNIS PEMBIBIHAN DAN PEMBERIAN PEMBERIAN TERNAK DI TABANAN - Nyoman Yudiarini; Luh Putu Kirana Pratiwi; Ida Ayu Made Dwi Susanti (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2022)
Chicken livestock is one type of business that has the potential to be developed, besides being profitable in the business sector, it is also able to preserve Indonesian germplasm. Several factors that support the domestic chicken business can be developed, because the demand for native chicken, especially in Bali, is still very potential to be developed in terms of consumption and fulfillment of religious ceremony facilities for the Hindu community in Bali. The aims of this study were 1) Analyzing the potential feasibility of domestic chicken business, 2) Knowing the inhibiting factors in the management of domesticated chicken production at the Baturiti Animal Husbandry and Animal Feed UPTD. The method used in this research is the method of R/C Ratio analysis and description analysis. The results showed that 1) the domestic chicken business was in a proper position with a value of 1.30 and 2). The inhibiting factors for the development of domestic chicken business are limited marketing, livestock disease attacks, high feed prices, limited labor, and minimal number of Day Old Chicken (DOC). To develop a domestic chicken business that is more profitable on a large scale, a breeding industry is needed that provides quality DOC, a programmed biosecurity system and a sustainable market arrangement